Green heterogeneous catalyst for biodiesel synthesis - Yung, K.F. (Progress in Nutrition, 2011)
SummaryThe depletion of fossil fuel and global warming are major environmental concerns in recent decades and alternative sources of energy like solar, wind, hydro, biomass and even nuclear has been extensively studied by different scientists as potential solutions. However, one important problem associated with the running out of fossil fuel is normally overlooked i.e. the cease of chemical raw materials supply for plastics, medicine and other fine chemicals. Among all, biomass is the only hope that would harvest energy from sun with the cogeneration of important raw materials for our future. Also, due to its carbon neutrality, non toxicity, biodegradability and compatibility with the existing infrastructures for oil refinery and transportation system, biofuel has become a promising alternative as liquid transportation fuel. Catalizzatore verde eterogeneo per la sintesi di biodieselRiassuntoL’esaurimento dei combustibili fossili e il riscaldamento globale sono i principali problemi ambientali degli ultimi decenni; numerosi scienziati stanno studiando fonti di energia alternative come possibili soluzioni (ad esempio energia solare, eolica, idroelettrica, a biomassa e persino nucleare). Tuttavia, un importante problema, associato con l’esaurimento dei combustibili fossili, viene normalmente trascurato e cioè porre fine alla richiesta di materie prime chimiche per la plastica, la medicina e altri prodotti della chimica nobile. Tra tutti, la biomassa è l’unica speranza per raccogliere energia dal sole con la co-generazione di importanti materie prime per il nostro futuro. Inoltre, i biocarburanti, grazie al loro carbonio neutro, non tossico, biodegradabile e compatibile con le infrastrutture esistenti per la raffinazione del petrolio e per il sistema di trasporto, sono diventati una promettente alternativa come combustibile liquido per i trasporti.